TELAAH KONFLIK PENGUKUHAN RAJA PEREMPUAN DI KERATON YOGYAKARTA (DALAM TINJAUAN SOSIOLOGIS) - Febriani, Nita Putri (Studi Budaya Nusantara, 2023)
Under the leadership of Sultan Hamengku Buwono (HB) X, the Yogyakarta Sultanate was faced with internal palace conflicts, namely between the royal family itself and the sultan's younger siblings. This was as a result of the words of the king who bestowed the title Mangkubumi on Gusti Kanjeng Ratu (GKR) Pembayun. The pinning of this title indicated that the eldest daughter of the sultan HB X had been officially appointed as the crown princess, who would later continue the reign of the palace if the sultan died. However, the king's words were strongly opposed by the sultan's brothers, because they were considered to be contrary to the traditions of the Yogyakarta Palace. The reason is that so far from Hamengkubuwono I to Hamengku Buwono X, the palace has always been led by a king (son), especially if you remember that the Yogyakarta Palace is part of the Islamic Mataram Kingdom. Judging from its history, the succession to the leadership of the Yogyakarta Palace has not always been smooth. Many conflicts and clashes of interests occurred between various parties. This phenomenon is inseparable from the attitudes and desires of every royal descendant who feels entitled to become the next heir to power. This study aims to focus on discussing the conflicts that occur by analyzing Dahrendorf's power conflict theory, as well as all changes due to the king's words that are against traditional rules (paugeran palace) which have an impact on conflict and its influence on the perspective of the people of Yogyakarta in particular.